The Activity of Natural Polymorphic Variants of Human DNA Polymerase β Having an Amino Acid Substitution in the Transferase Domain - Olga A. Kladova; Timofey E. Tyugashev; Elena S. Mikushina; Nikita A. Kuznetsov; Daria S. Novopashina; Aleksandra A. Kuznetsova (Cells, 2023)
To maintain the integrity of the genome, there is a set of enzymatic systems, one of which is base excision repair (BER), which includes sequential action of DNA glycosylases, apurinic/apyrimidinic endonucleases, DNA polymerases, and DNA ligases. Normally, BER works efficiently, but the enzymes themselves (whose primary function is the recognition and removal of damaged bases) are subject to amino acid substitutions owing to natural single-nucleotide polymorphisms (SNPs). One of the enzymes in BER is DNA polymerase β (Polβ), whose function is to fill gaps in DNA with complementary dNMPs. It is known that many SNPs can cause an amino acid substitution in this enzyme and a significant decrease in the enzymatic activity. In this study, the activity of four natural variants of Polβ, containing substitution E154A, G189D, M236T, or R254I in the transferase domain, was analyzed using molecular dynamics simulations and pre-steady-state kinetic analyses. It was shown that all tested substitutions lead to a significant reduction in the ability to form a complex with DNA and with incoming dNTP. The G189D substitution also diminished Polβ catalytic activity. Thus, a decrease in the activity of studied mutant forms may be associated with an increased risk of damage to the genome.